Antecedents and Consequences of Partner Phubbing: Systematic Literature Review - Wahyu Putri; ⁠Nida Hasanati (Penerbit Jurnal Indonesia, 2026)
This study aims to examine the antecedents and consequences of partner phubbing based on empirical findings published in the last five years. This study uses a systematic literature review with the SPIDER approach. The review applies inclusion and exclusion criteria. The literature search uses Publish or Perish 8 with Google Scholar and journal databases including PubMed, Sagepub, ResearchGate, Scopus, ScienceDirect, and Elsevier. The review results show that antecedents of partner phubbing are dominated by individual psychological factors. These factors include loneliness, attachment anxiety, low self-esteem, low empathy, fear of missing out, and addiction to gadgets and social media. Relational factors also contribute to partner phubbing behavior. These factors include low intimacy, ineffective communication, increased conflict, and low partner responsiveness. The findings also indicate that partner phubbing has negative consequences for romantic relationships. Short-term effects include sadness, anger, irritation, and feelings of loneliness. Long-term effects include increased jealousy and conflict, reduced commitment, decreased intimacy, weakened trust, lower relationship satisfaction, and reduced individual well-being. These impacts can undermine relationship stability and quality. This review provides a structured overview of recent evidence on partner phubbing and highlights key psychological and relational mechanisms that explain its causes and consequences.